2017
DOI: 10.1136/bmjophth-2016-000046
|View full text |Cite
|
Sign up to set email alerts
|

Physical inactivity in relation to self-rated eyesight: cross-sectional analysis from the English Longitudinal Study of Ageing

Abstract: BackgroundTo assess the cross-sectional association between self-rated eyesight and physical activity behaviour in a large general population sample of older English adults.MethodsAnalyses of data from the English Longitudinal Study of Ageing. Participants provided information on self-rated eyesight (categorised as: excellent/very good/good/fair–poor) and their own physical activity levels (categorised as: inactive/moderate only at least 1/week, vigorous at least 1/week). Associations between self-rated eyesig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 30 publications
5
40
1
1
Order By: Relevance
“…Finally, we also found significant associations between lower levels of active travel and hearing problems and visual impairments. A previous study in older English adults demonstrated that those with self-rated poor vision were over twice as likely to be physically inactive than those who reported having excellent vision [ 57 ]. Lack of physical activity may increase the likelihood of other metabolic diseases such as diabetes, which in turn may lead to severe sight-threatening issues if not controlled adequately, although more research is needed to confirm this hypothesis [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also found significant associations between lower levels of active travel and hearing problems and visual impairments. A previous study in older English adults demonstrated that those with self-rated poor vision were over twice as likely to be physically inactive than those who reported having excellent vision [ 57 ]. Lack of physical activity may increase the likelihood of other metabolic diseases such as diabetes, which in turn may lead to severe sight-threatening issues if not controlled adequately, although more research is needed to confirm this hypothesis [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor eyesight is related to lower levels of physical activity in older adults (20), which in turn increases risk of diseases such as type 2 diabetes that is associated with further visual problems manifesting throughout the lifespan (33). It is important to intervene in this selfperpetuating barrier in childhood activity levels to reduce disease risk and increase quality of life in those with visual problems.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that hearing problems are not key barriers to physical activity. It is important to examine the progression of fitness and physical activity of children with hearing problems throughout the lifespan, and into old age, where sensory deficits are again associated with lower levels of physical activity (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the management of obesity, poor ocular health may be of concern as it may increase physical inactivity. 57 Finally, future studies of longitudinal design are warranted to corroborate our findings, to gain a better understanding of the potential causality of the associations between obesity and ocular health, and to identify mediators involved in these relationships.…”
Section: Clinical Implications and Directions For Future Researchmentioning
confidence: 57%